Teaching Strategies Guru PAI dalam Mengembangkan Pembelajaran CERIA Bagi Siswa di SMAN 1 Rundeng - Muhaddis, Muhaddis (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2024)
This study aims to explore the teaching strategies of Islamic Religious Education (PAI) teachers in developing CERIA learning for students at SMAN 1 Rundeng. Using a qualitative approach, data was collected through interviews and observations involving school principals, teachers, and students. The findings reveal that the teaching strategies implemented by PAI teachers focus on enhancing scientific concepts through various interactive and engaging teaching models. The study also identifies several challenges, including the limited application of teaching strategies, minimal scientific concept development, lack of facilities and technology, the absence of a PAI laboratory, insufficient parental involvement, and inadequate school support. To overcome these challenges, collaboration between teachers and parents needs to be strengthened to enhance the effectiveness of CERIA learning in scientific concepts.